2020
DOI: 10.1111/jvim.15738
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag treatment of a dog with idiopathic aplastic pancytopenia

Abstract: Idiopathic aplastic pancytopenia is an uncommon disease in dogs which results in pancytopenia and for which an immune‐mediated etiology is suspected. A small number of affected dogs reported in the veterinary literature have responded to immunosuppressive medication but the prognosis generally is considered poor with a reported mortality rate of 80%. Reported response rates to immunosuppression alone in affected people are low with overall and complete responses of 65 and 10%, respectively. With the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…A recent case report in the veterinary literature indicated that eltrombopag may have been beneficial in the treatment of a dog with idiopathic aplastic pancytopaenia 29 . In the case described by Kelly et al, 29 and in the human literature a sustained response was seen following the discontinuation of the drug following two months of treatment. In our case, the dog was treated with eltrombopag for eleven days.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent case report in the veterinary literature indicated that eltrombopag may have been beneficial in the treatment of a dog with idiopathic aplastic pancytopaenia 29 . In the case described by Kelly et al, 29 and in the human literature a sustained response was seen following the discontinuation of the drug following two months of treatment. In our case, the dog was treated with eltrombopag for eleven days.…”
Section: Discussionmentioning
confidence: 98%
“…The dose used in this case (25 mg once daily in a 28 kg dog) was 0.9 mg/kg. In the case by Kelly et al, 29 a dose of 1.25 mg/kg was used with no apparent adverse effects, showing there is scope for a higher dosage to be safely used in canine patients. Further studies are required to confirm or refute the hypothesis that eltrombopag may play a role in the treatment of myelosuppression and thrombocytopenia in veterinary patients, and to find the correct dosage for dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Duration of treatment with eltrombopag in veterinary patients should be established. The case presented by Kelly et al 14 received eltrombopag for 2 months based on a previous study in human patients. 1 In human patients, eltrombopag is usually administered for 6 months or more.…”
Section: Discussionmentioning
confidence: 99%
“…The case described by Kelly et al 14 received cyclosporin and prednisolone at the same time as eltrombopag, making it difficult to establish if the response was secondary to the eltrombopag or a combination of eltrombopag with immunosuppressive drugs. In the case described by Aspinall et al 15 , a granulocyte-macrophage colony-stimulating factor was used in combination with eltrombopag.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation